Comprehensive geriatric assessment in elderly patients with dementia. Issue 1 (27th August 2014) - Namioka, Nayuta; Hanyu, Haruo; Hatanaka, Hirokuni; Fukasawa, Raita; Sakurai, Hirofumi; Iwamoto, Toshihiko
<x xml:space="preserve">Abstract</x> Aim We have recently developed and validated a screening test for comprehensive geriatric assessment (CGA) named "Dr. SUPERMAN". We compared the results obtained by the CGA of patients with Alzheimer's disease (AD), vascular dementia (VaD) and dementia with Lewy bodies (DLB), and determined the relationship between functional deficits and clinical characteristics in each type of dementia. Methods We used Dr. SUPERMAN to examine patients with AD (24 men and 53 women, mean age 83.0 ± 5.1 years), VaD (10 men and 12 women, mean age 80.4 ± 5.0 years) and DLB (28 men and 20 women, mean age 81.2 ± 5.5 years). Results Patients with DLB or VaD had functional deficits more frequently than those with AD in many fields. Significant correlations between functional impairments and clinical characteristics, such as age, sex and Mini‐Mental State Examination scores, in the non‐AD group (including DLB and VaD) were found in more extensive fields than those in the AD group. Conclusions Patients with dementia, particularly DLB, have several geriatric problems. Correlations between functional deficits and clinical characteristics differ between the AD group and the non‐AD group. Non‐AD patients of older age who are male and have advanced dementia are more likely have several functional deficits. In addition to age and severity of dementia, the type of dementia should be considered in the treatments and interventions of elderly patients with dementia. Geriatr Gerontol Int 2015; 15: 27–33.